An Analysis of Cost Management Strategies Employed By Building Contractors on Projects in Zimbabwe - Chigara, Benviolent; Moyo, Tirivavi; Mudzengerere, Fungai Hamilton (International Journal of Sustainable Construction Engineering and Technology, 2013)
The construction industry is a major consumer of capital resources by virtue of the magnitude, complexity and nature of the works it executes. Yet improving cost performance still remains a chronic challenge facing the construction industry worldwide. Apart from advances made by contractors to devise mechanisms to manage project cost, studies across the world reveal that construction projects are hardly completed within budget. The Zimbabwean construction industry has not been spared either. However, this background is considered unhealthy for an industry whose capital consumption is heavy and concomitant cost overruns spell disastrous financial consequences on the investor. This study explored cost management strategies employed by contractors on building projects and also investigated the challenges that contractors encounter in managing project cost. Exploratory research design was employed making use of both questionnaires and interviews to collect data from selected contractors registered under category A, B and C of the Construction Industry Federation of Zimbabwe (CIFOZ). The study observed that in the majority of cases, contractors’ efforts to manage projects costs are centred on management of project resources. Additionally, monthly cost reports, variance management, project budgets and cash flow forecasting are among the other strategies. However,  in spite of the growing trend to automate cost control systems, there is evidence to suggest that the traditional paper based systems of storing and managing information is widely used in the industry. Contrary to having cost management systems in place, contractors admit experiencing cost overruns on their projects. These cost overruns are attributable to organizational related challenges, shortage of skilled personnel, and unavailability of some building materials on the local market, variations and deficiency in cost control systems